2018
DOI: 10.15850/amj.v5n2.1420
|View full text |Cite
|
Sign up to set email alerts
|

Young to Middle-Aged Adults and Low Education: Risk Factors of Spondylitis Tuberculosis with Neurological Deficit and Deformity at Dr. Hasan Sadikin General Hospital

Abstract: Background: Incidence of tuberculosis has risen again, including extrapulmonary tuberculosis. Spondilitis tuberculosis is one the most commonly encountered which can cause disability and even death. The aim of this study was to evaluate characteristics of spondilitis tuberculosis patients and probable risk factors. Methods: This was a descriptive, cross sectional study from all medical records of spondylitis tuberculosis patients at Dr. Hasan Sadikin General Hospital from January 2012 to December 2013. Variabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Another study by Ismiarto et al . 22 reported that young adults are the most commonly affected by TB spondylitis in endemic areas. However, in developed countries, it is more common in older people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study by Ismiarto et al . 22 reported that young adults are the most commonly affected by TB spondylitis in endemic areas. However, in developed countries, it is more common in older people.…”
Section: Discussionmentioning
confidence: 99%
“…Previous support reported that 94.9% of TB spondylitis patients were found to have neurological deficits (sensory and motor). Neurological examination may show motor or sensory function changes in the extremities 22 .…”
Section: Discussionmentioning
confidence: 99%
“…The incidence also increases in populations experiencing malnutrition, dense and slum areas, low levels of education, and poor sanitation. This condition is common in developing countries[ 14 ]. The prevalence of spondylitis TB increases in patients with certain conditions and comorbidities, such as pulmonary TB, previous history of TB infection, history of long-term glucocorticoid treatment, DM comorbidity, chronic kidney disease, and human immunodeficiency virus infection.…”
Section: Discussionmentioning
confidence: 99%
“…This means that the majority of less prosperous people can only obtain education to that level, which is still considered as a low educational level. This can lead to lower awareness around maintaining sanitation and environmental hygiene, which is reflected in the finding that the majority of TB patients are still disposing of their sputum carelessly (Ismiarto, Tiksnadi, & Soenggono, 2018).…”
Section: Discussionmentioning
confidence: 99%